The Relationship Between Maternal Anaemia, Low Birth Weight And LBW History With The Incidence Of Stunting In Young Children In The Lubuk Sanai Health Centre Working Area - Andhela, Mia; Jumita, Jumita; Situmorang, Ronalen Br (Jurnal Kesehatan Mitra Sekawan, 2024)
According to the results of the Ministry of Health's Indonesian Nutritional Status Study (2022), the prevalence of toddlers experiencing stunting in Indonesia is 21.6%. The Lubuk Sanai Community Health Center's incidence of stunting among toddlers in 2022 is 78 cases. This study aims to determine the relationship between anemic pregnant women and a history of LBW with the incidence of stunting in children under five in the Lubuk Sanai Health Center Working Area, Mukomuko Regency in 2023. This research was conducted using a case control design with a retrospective nature. The sampling technique involved a total sampling of 50 people. The sample cases in this study were 50 stunted toddlers. The control sample in this study was toddlers who were not stunted. Data analysis consists of univariate and bivariate analysis. The results of this study found that there were 50 people (50%) of respondents who experienced stunting and 50 people (50%) of respondents who did not experience stunting, there were more than half of the 75 (75%) respondents who did not experience anemia during pregnancy, there were more Of the 76 (76%) respondents who were not CED during pregnancy, almost all 96 (96%) respondents were not LBW. The results of the Chi-Square statistical test are that there is no significant relationship between the history of anemia in pregnant women and the incidence of stunting p value (0.106), in pregnant women KEK p value (1.000) and there is a significant relationship between the history of LBW and the incidence of stunting p value 0.041)Researchers suggest that health workers at the Community Health Center provide education and assistance to mothers about stunting prevention from an early age, from teenagers to pregnant women.